How to Run a Writing Workshop? On the Cultivation of Scholarly Ethics in 'Global' Legal Education. Issue 2 (3rd July 2018) - Chiam, Madelaine; Pahuja, Sundhya; Parker, James E.K.
Abstract: This article does two main things. First, it records and shares a methodology for running a writing workshop in the context of transnational doctoral and post-doctoral legal education. Second, it offers a critical reflection on this methodology, and in doing so draws out some more general lessons for thinking about our roles as scholars and teachers in the contemporary university. Our thesis is that the unusually formal, even stylised, structure of the writing workshops we describe not only offers participants an opportunity for detailed feedback on their work, but also helps to foster a certain ethics of scholarly conduct. This ethics emphasises the intimacy of scholarly relations on the one hand, and the importance of listening on the other. Such an ethics may be antithetical to some of the more insidious imperatives of the contemporary university.